Perceived behavioral traits as key determinants of entrepreneurial intention in higher education institutions - Sandoval Álvarez, Carlos Alberto (2023)
Abstract: This article examines how a business school's environment encourages the formation of entrepreneurial intentions among its students. Building on insights from the theory of planned behaviour and the business event model, a structural equation model was applied on a sample of 283 Costa Rican university students. The main results of the study suggest that the entrepreneurial training provided by the business school contributes to improve students' entrepreneurial intentions. However, this effect develops through an indirect mechanism: that is, entrepreneurial training positively influences students’ attitudes toward entrepreneurship which, in turn, impact students’ perception on entrepreneurial self-efficacy. The proposed model rooted in cognitive frameworks allows business schools, and higher education institutions in general, to measure and evaluate the effectiveness of their entrepreneurial training programs in promoting entrepreneurial intentions.